Structure and reactivity of NO/NO+/NO− pincer and porphyrin complexes - Gallego, Cecilia Mariel (2021)
This review covers recent progress in the field of nitrosyl pincer and porphyrinate complexes, and how their reactivity depends on the redox state of the NO ligand. Synthetic methods, and the most significant structural information, spectroelectrochemical studies, and different reactivities of nitrosyl pincer complexes are presented. These include selective activation and functionalization of carbon-halogen bonds, catalysis for a variety of specific organic reactions, mediation of NO disproportionation and reversible coordination of solvents and weakly-coordinating anions. Regarding the porphyrinate complexes, the focus is on biorelevant nitroxyl (NO−/HNO) complexes, discussing pioneering studies along with preparation and common characterization methods. Their relative stability in different conditions is compared, and possible decomposition mechanisms are discussed in terms of their ability to act as biomimetic models for enzymatic systems.